Pengaruh Penambahan Limbah Plastik Sebagai Alternatif Pengganti Bata Beton Dinding Rumah - Prabowo, Dian; Hardini, Probo; Kurniawan, Ipung; Santoso, Agus (Accurate: Journal of Mechanical Engineering and Science, 2022)
The current handling of waste, especially styrofoam, plastic, used oil is not optimal, these wastes can be used to manufacture other products such as bricks with a simple process. If the waste is processed properly, it will get good economic value. To get a good value or product, it is necessary to do research or testing, as in this study, namely the use of styrofoam waste, plastic and used oil to be used as bricks. In this study, it is hoped that the public will understand and understand the quality of the types of composite bricks and ordinary types of bricks seen from their advantages and disadvantages. Styrofoam waste, plastic and used oil are mixed into bricks with a volume of 21.27%. The equipment used in this research are chopper, stirrer, digital balance and compression test machine. In this study, the results of the III (composite) molded bricks decreased the compressive strength of 59% compared to mortar and cement bricks. The results of the compressive strength test in mold III (composite) were 47.76% higher than that in mold II on composite brick. Composite III bricks are classified as quality III, namely with solid type bricks that cannot get a large load.